FISH SUPPLY BENGKALIS AND DISTRIBUTION IN DURI MARKET SUBDISTRICTREGENCY OF RIAU PROVINCE - Bobby Kurniawan; Hendrik Hendrik; Darwis AN Darwis AN (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2019)
ABSTRACT This study aims to find where the supply of fish in Duricame from, Duri City is a city with poor water conditions resulting in a lack of fish supply originating from the area itself, while people's demand for fish exceeds the supply of supplies originating from the Duri area. Therefore, to meet the needs of the community in consuming fish, the distribution of fish from outside the region was carried out so that the fish supply in the Market of Duri was able to meet the demands of the community. Data analysis using descriptive analysis, the method used in this study is the survey method, the data collected includes primary data and secondary data. Primary data is obtained from collector traders through direct interviews using prepared questionnaires, while secondary data is obtained from related agencies. Fish marketed in Denai are imported market from various regions including sea water fish supplied in the Denai market came from the Aceh region, Sibolga, TanjungBalaiKarimun, Riau Islands, and West Sumatra. While freshwater fish supplied in the Denai market come from Maninjau, TalukKuantan, Kampar, KampungPatin. The fish supplied in the Denai Market consist of sea water fish such as sarai, big fish, tuna, tuna, ray fish, gambolo fish, belida fish, baung fish, selais fish. Whereas freshwater fish consists of cork fish, tilapia, eel, gouramy fish, sepat fish, siamsepat fish, catfish, catfish and betok fish. The fish supplied in the Denai market are imported every day with amount of 5,31 tons every day.Keywords: Fish Supply, Distribution, Denai Market, Mandau District